2008
DOI: 10.1016/j.resp.2008.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-1 regulates ozone-enhanced tracheal smooth muscle responsiveness by increasing substance P (SP) production in intrinsic airway neurons of ferret

Abstract: Exposure to ozone induces airway hyperresponsiveness (AHR) mediated partly by SP released from nerve terminals of intrinsic airway neurons. Our recent studies showed that IL-1, an important multifunctional proinflammatory cytokine, increases synthesis and release of SP from intrinsic airway neurons. The purpose of this study is to investigate the possible involvement of endogenous IL-1 in modulating neural responses associated with ozone-enhanced airway responsiveness. Ferrets were exposed to 2 ppm ozone or fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 46 publications
1
22
0
1
Order By: Relevance
“…Irritant exposure during this developmental phase may be a predisposing factor to the pathogenic mechanisms leading to neurogenic inflammation (41). In ferret, we have shown that increased SP innervation after O 3 exposure is associated with increased airway smooth muscle responsiveness (31,42,43). In rat, SP contracts airway smooth muscle and increases vascular permeability (13,40).…”
Section: Discussionmentioning
confidence: 94%
“…Irritant exposure during this developmental phase may be a predisposing factor to the pathogenic mechanisms leading to neurogenic inflammation (41). In ferret, we have shown that increased SP innervation after O 3 exposure is associated with increased airway smooth muscle responsiveness (31,42,43). In rat, SP contracts airway smooth muscle and increases vascular permeability (13,40).…”
Section: Discussionmentioning
confidence: 94%
“…The nodose ganglia were then frozen in isopentane, cooled with liquid nitrogen, and stored in airtight bags at -80 C. Immunocytochemical procedures for localisation of substance P immunoreactive neurons were similar to those described previously (Wu et al 2008). Briefly, cryostat sections (12 mm thickness) of nodose ganglia were mounted on gelatin-coated coverslips, dried briefly at room temperature and then incubated with rabbit anti-substance P antiserum (Peninsula, Belmont, CA, USA) at a dilution of 1:100 for 60 min in a humidified chamber at 37 C. The coverslips were rinsed with a PBS-Tx containing 1% bovine serum albumin (PBS-Tx + BSA) three times, for 5 min per rinse.…”
Section: Substance P Immunohistochemistrymentioning
confidence: 99%
“…The quantitative measurement of fluorescence intensity in nodose ganglia was similar to as describedpreviously (Wu et al 2008). Briefly, we recorded images using an AX70 microscope (Olympus America, Melville, NY, USA) with the SPOT 2 digital camera (Diagnostics Instruments, Sterling Heights, MI, USA).…”
Section: Substance P Immunohistochemistrymentioning
confidence: 99%
“…This allowed us to easily quantify a very sparsely and unevenly distributed set of structures-the instrinsic airway ganglia-which in previous studies required laborious tissue sampling (22,(36)(37)(38). We also pushed the limit of our technique by quantifying a rarer subset (15% total ganglia) that expresses substance P, which is implicated in lung disease and airway hyperresponsiveness (38,39). This low sampling probability of substance P may explain contradictory findings of the presence of substance P in human intrinsic ganglia (36,37).…”
Section: Full-thickness Human Tracheal Innervation and Modeling Tissumentioning
confidence: 99%